Assembly of high-performance hybrid supercapacitors using FeCo2O4 microflowers as battery-type cathode materials. Issue 7 (1st April 2023) - Li, Zhizhen; Wu, Runze; Bao, Enhui; Du, Shouxiu; Xu, Chunju; Zhu, Jiang; Mao, Hui; Chen, Huiyu
Abstract: In this work, FeCo2 O4 microflowers (MFs) and microparticles (MPs) were respectively prepared at different temperatures via a wet chemical method, along with a post annealing treatment in air. These MFs and MPs exhibited huge specific surface area and a large number of mesopores. Several electrochemical tests were conducted in a three-electrode configuration. The FeCo2 O4 MFs delivered a specific capacity of 301.3C g −1, higher than 253.9C g −1 for FeCo2 O4 MPs. A hybrid supercapacitor (HSC) device was assembled with FeCo2 O4 as cathode and activated carbon (AC) as anode to investigate the practical applications in electrochemical energy storage. The FeCo2 O4 MFs//AC HSC delivered a capacity of 107.2C g −1 at 1 A g −1 and an energy density ( E d ) of 25.7 W h kg −1 at 862.6 W kg −1, respectively, while the FeCo2 O4 MPs//AC HSC showed an E d of 23.8 W h kg −1 at the power density ( P d ) of 878.9 W kg −1 . The two HSCs showed little capacity decay after 3000 cycles at 6 A g −1 . The capacity of FeCo2 O4 MFs and the obtained E d of HSC were in a high status among those of transition metal oxides (TMOs)-based electrodes reported earlier. The current synthetic strategy can be used as a reference to the synthesis of other similar electrochemical materials for HSC electrodes. Graphical abstract: FeCo2 O4 microflowers were prepared via a wet chemical method with a post annealing treatment of precursor. These microflowers exhibited battery-type electrochemical response with a high capacity of 301.3C g −1 at 1 A g −1 in 2 M of KOH electrolyte. The assembled FeCo2 O4 microflowers//AC hybrid supercapacitor delivered a high energy density of 25.7 W h kg −1 at the power density of 862.6 W kg −1 . Image 1 Highlights: FeCo2 O4 microflowers were prepared via a two-step synthetic method. A high specific capacity of 301.3C g −1 at 1 A g −1 was obtained. 72.4% rate capability was reached with current density increasing from 1 to 10 A g −1 . The HSC device delivered an energy density of 25.7 W h kg −1 at 862.6 W kg −1 .